APLIKASI SISTEM INFORMASI PENGAJUAN CUTI BERBASIS WEBSITE “SIPECUT” - Dhea Yuniar Achmad; Amaliyah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
The competitive era of Industrial Revolution 4.0 is characterized by the development of progress in all fields of activity, with companies and authorities competing to keep up with the changes through the use of information technology. One of the most popular information technology implementations in enterprises is the employee information system for vacation. A manual leave application system is still used to apply for leave at the East Java provincial government office. An employee who wants to apply for leave must first print the leave form, fill out the leave form, and then give the leave form to the employee for manager approval. The manual process slows down the process of requesting time off. The purpose of this research is to address the shortcomings of the current manual system and create a web-based leave request information system aimed at simplifying and speeding up the employee leave request process. The research method used by researchers in this study is a qualitative descriptive method. This web-based leave request information system can be used to assist employees in requesting leave and make it easier for companies to process and manage leave data.